Sistema multicanal de sensores resistivos para medição de escoamentos bifásicos - Machado, Diogo Teixeira (2013)
Two-phase flows are commonly found in many industry branches, such as in oil and gas production, nuclear power plants and chemical reactors. The monitoring of such flows is very important since they are often involved in efficiency and safety issues of plants and processes. The focus of this work is in gas liquid two-phase flows, as they are the most common type in the oil and gas production activities. Different measuring techniques are available to experimentally investigate two-phase flows. In this work, the design and construction of a two-wire resistive sensor system is presented. The sensor system is based on electrical conductivity measurements which means that it is possible to discriminate the two phases within a flow since they present different electrical properties. The resistive sensor system is of relatively low cost, high time resolution and minimally invasive. It was projected to be installed in a test facility with 26 mm inner diameter. The system comprises of up to 16 two-wire resistive sensors, a microcontrolled hardware for signal generation and acquisition, and a software for data processing and visualization. Based on static reference measurements adjustment curves for each resistive sensor was obtained. The developed system was comparatively evaluated against high-speed camera measurements, showing satisfactory results. Hence, the system may be well deployed in experimental studies of two-phase flows.